NetBeans Ruby and Rails IDE with JRuby - Kutler, Chris; Leonard, Brian (Apress : Imprint: Apress, 2009)
As Ruby and Rails continues to grow, and more and more jobs are coming online that require you to effectively develop Ruby and Rails in the web tier. Beyond the Rails framework, there are still very few proven tools and IDEs to get the job done, at least until now. The NetBeans Ruby and Rails IDE, according to some, is by far the best and proven IDE in Ruby and Rails. Who would've thought a Java IDE could do Ruby and Rails? Published with the developer in mind, firstPress technical briefs explore emerging technologies that have the potential to be critical for tomorrow's industry. Apress keeps developers one step ahead by presenting key information as early as possible in a PDF of 150 pages or less. Explore the future through Apress with NetBeans™ Ruby and Rails IDE with JRuby, an officially endorsed NetBeans project book, which is for Ruby and Rails programmers who want to take advantage of the NetBeans IDE to facilitate their Ruby and/or Rails web application development. Shows you how to use the NetBeans IDE 6.5 in the Ruby and Rails development processes Gives you in-depth information to help you configure the working environment for your specific Ruby interpreter, application server, and database server Showcases the NetBeans features that enhance your productivity from project creation, to editing, debugging, and testing Authors Chris Kutler and Brian Leonard work closely with both the developers of the NetBeans Ruby and Rails IDE project and the user community. The authors' in-depth knowledge of the numerous product features, in addition to an understanding of how the community uses the product to meet their development practices, enables them to present you the essential information necessary to efficiently and effectively use the tools of this IDE.